Technology of Future Ecologists’ Preparation in the Natural Sciences through the Use of Informational Educational Environment Moodle - Halyna Biletska (Pedagogical Discourse, 2014)
The article deals with the technology of natural scientific preparation of future ecologists through the use of informational educational environment Moodle. It has been substantiated that the developed technology facilitates mastering the knowledge in the sphere of natural sciences, increases motivation in learning natural science disciplines, provides the formation of skills and expertise in applying the knowledge of natural sciences to tackle professional tasks, develops individual autonomy, activeness, creativity and other personal qualities, which help to achieve success in professional ecological activity and social life on the whole. Thus, the proposed technology provides the achievement of the estimated result of natural scientific preparation, which lies in the formation of future ecologists’ natural sciences competence.